SELEKSI DAN UJI ANTAGONISME TRICHODERMA SPP. ISOLAT TAHAN FUNGISIDA NABATI TERHADAP PERTUMBUHAN PHYTOPHTHORA CAPSICI - Joko Prasetyo, Efri & Radix Suharjo . (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2009)
Screening and testing of isolate of Trichoderma spp. resistant to botanical fungicides on the growth of P. capsici. The research was conducted at the Plant Disease laboratory, Plant Protection Department, Faculty of Agriculture, Lampung University from March – November 2007. The aim of the research was to find isolate of Trichoderma spp. resistant to botanical fungicide which still have its capability to inhibit the growth of P. capsici. Completely randomized design with three replicates was used in the research. Data collected in this research were isolates of Trichoderma spp. resistant to botanical fungicides and inhibition percentage of isolates of Trichoderma spp. resistant to botanical fungicide on the growth of P. capsici. The data were analysed with anova and continued with LSD test at 5% of significant level. As much as 9 isolates of Trichoderma spp. resistant to botanical fungicide were found. Three isolates of T. viride could survive in the 100% of tumeric powder (C), east indian galangale powder (A), and clove leaf powder (B). Two isolates of T. harzianum could survive in the 100% of tumeric powder (A) and clove leaf powder (A). One isolate survived in the 90% of east indian galangale powder (D). Two isolates of T. koningii also could survive in the 100% of tumeric powder (A) and clove leaf powder (A). One isolate survived in the 90% of east indian galangale powder (C). All of the isolates inhibited P. capsici. All of the isolates found statistically had the same capability to inhibit the growth of P. capsici.